The EDA/EDAR/NF-κB pathway in non-syndromic tooth agenesis: A genetic perspective - Yanzi Gao; Yanzi Gao; Xiaohui Jiang; Zhi Wei; Zhi Wei; Hu Long; Hu Long; Wenli Lai; Wenli Lai (Frontiers in Genetics, 2023)
Non-syndromic tooth agenesis (NSTA) is one of the most common dental developmental malformations affected by genetic factors predominantly. Among all 36 candidate genes reported in NSTA individuals, EDA, EDAR, and EDARADD play essential roles in ectodermal organ development. As members of the EDA/EDAR/NF-κB signaling pathway, mutations in these genes have been implicated in the pathogenesis of NSTA, as well as hypohidrotic ectodermal dysplasia (HED), a rare genetic disorder that affects multiple ectodermal structures, including teeth. This review provides an overview of the current knowledge on the genetic basis of NSTA, with a focus on the pathogenic effects of the EDA/EDAR/NF-κB signaling pathway and the role of EDA, EDAR, and EDARADD mutations in developmental tooth defects. We also discuss the phenotypic overlap and genetic differences between NSTA and HED. Ultimately, this review highlights the importance of genetic analysis in diagnosing and managing NSTA and related ectodermal disorders, and the need for ongoing research to improve our understanding of these conditions.